Beyond Survival: An Autoethnographic Understanding of Adult Survivors of Child Sexual Abuse - Halimatussa’diah, Diyanah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This article explores the complex and multifaceted journey of adult survivors of child sexual abuse using an ethnographic methods to provide an alternate and intimate perspective regarding sexual abuse and tells about emotional, psychological, and cultural implications of the abuse. The research combined personal narratives and academic analysis of the author’s experience and other respondents with shared experience. The study reflects on the long-term effects of trauma, including the process of healing, journey to meaning making and finding closure. The research highlights the importance of self-reflection, storytelling, and examines the societal challenges and stigmas that survivors face. The research aimed to highlight the significant difference in disclosing personal trauma experiences as a form of healing. The method uses autoethnography through archive analysis written by adult survivors of child sexual abuse as means for collective healing and peer support. By offering an autoethnographic lens, the study aim to fosters deeper understanding of how adult survivors of child sexual abuse navigate their lives beyond survival, ultimately seeking to reclaim their identities and reframe their narratives which used to be dominated by men’s perspectives. The result shows that the people involved in this collective ethnography have increased their self-acceptance through having disclosure of their experiences.